Cognitive Fragility in Newtonian Problem Solving: A Critical Examination of Metacognitive Monitoring and Evaluation Processes - Dewi Diana Paramata; Mursalin Mursalin; Astin Lukum; Masra Latjompoh; Frida Maryati Yusuf; Elya Nusantari; Masri Umar; Yosie Andriani (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Solving problems related to Newton’s laws of motion requires strong executive control over operational thinking processes. Empirical evidence, however, indicates that many students experience systemic fragility within their cognitive structures as a result of dysfunction in metacognitive regulation. This study aimed to identify and critically examine the extent of students’ cognitive fragility in solving Newtonian mechanics problems, with particular emphasis on the metacognitive functions of monitoring and evaluation. The study employed a qualitative approach using a descriptive-exploratory design with a critical diagnostic orientation. Data were collected from students in the Science Education Program at Universitas Negeri Gorontalo through the Newtonian problem solving ability test  and retrospective task-based clinical interviews. The data were analyzed interactively through the stages of data condensation, data display, and conclusion drawing. The findings revealed severe metacognitive dysfunction across both regulatory phases. During the monitoring stage, cognitive fragility appeared in the form of loss of visual anchoring to free-body diagrams, anomalies in assigning vector-coordinate signs, and a strong tendency to engage in jumping steps, which emerged as the most dominant type of error. At the evaluation stage, students’ reasoning was largely characterized by evaluation neglect and a superficial focus on outcome verification, where attention was limited to obtaining a final numerical answer. As a result, students frequently accepted physically unreasonable and anomalous solutions without engaging in self-correction or critical reflection. Overall, the study concludes that the collapse of students’ algebraic and physical reasoning stems directly from the breakdown of the feedback relationship between real-time monitoring and retrospective evaluation processes